Enlivening the promise of education : building collaborative learning communities through online discussion - Kaur , Kuldip (Idea Group Reference, 2007)
An important dimension in education is interaction, that is, the coming together of a number of people to discuss, debate, and deliberate about issues of common concern. In distance education, such social environments are as much present in online learning contexts as they are in face-to-face learning contexts such as tutorials. This chapter expands the notion of teacher student interaction to focus on integrating human computer interaction in the curriculum. This is done through the use of online discussion forums at Open University Malaysia that help build collaborative online communities using common principles of teaching and learning. Citing a recent case in point, this chapter demonstrates how the Open University Malaysia-Collaborative Online Learning Model for online interaction helped cultivate learner-centric virtual discussions and supported an interactive online community that showcased characteristics of social interdependence and instructional support. This chapter takes a social constructivist view of human computer interaction by proposing an instructional model supported by collaboration, guidance, interdependence, cognitive challenge, knowledge construction, and knowledge extension. The Introduction section of this chapter provides the rationale for human computer interaction and gives an overview of current-day perspectives on the online classroom. This is followed by a trenchant review of recent research on online interaction with a view to outlining the theoretical premise for the use of computers to develop thinking and collaborative or team skills. This section also provides a rationale for the use of online forums and gives a frame of reference for the role of the instructor in this enterprise. In the next section of this chapter, the Open University Malaysia-collaborative online learning model is described, with details on The Learning Context as well as Group Learning Outcomes, which may be seen as inherent parts of the model. Under the sub-section Knowledge Construction, the chapter carries a qualitative analysis of online interaction for one Open University Malaysia course using a comprehensive list of indigenous categories and sub-categories as well as examples of interactions that match each sub-category. The chapter ends with a Summary, a statement of Acknowledgement, a list of References, and an Appendix. The appendix contains the Task that was used for the course for which online interaction in this chapter was analyzed. (Author's abstract)